IMPLEMENTASI METODE MIND MAPPING DALAM AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS V DI SDN KARANGBANYU 1 - Reny Oktiana Dewi Erwanda; Yes Matheos Lasarus Malaikosa; Prima Rias Wana (Idaarah: Jurnal Manajemen Pendidikan, 2022)
Abstract: Implementation of the Mind mapping Method in Student Learning Activities in Class V Thematic Learning at SDN Karangbanyu 1 This study aims to determine the implementation of the mind mapping method in student learning activities in class V thematic learning at SDN Karangbanyu 1, namely regarding the planning, implementation and results of the implementation of the mind mapping method. The approach used in this research is qualitative descriptive qualitative type. The source of the research data was obtained from the principal, teachers, and fifth grade students at SDN Karangbanyu 1. The data collection techniques used observation, in-depth interviews, and documentation. Furthermore, in the analysis, from the data that has been obtained, the results of this research can be concluded that the application of the mind mapping method in the thematic learning of class V SDN Karangbanyu 1 has been going well. During the learning process, students seemed to be more active when using the mind mapping learning method and student learning outcomes also seemed to improve, although there were still some problems experienced by the teacher, namely the difficulty of explaining students who were left behind, such as finding it difficult to catch the explanations given by the teacher. In addition to the internal factors of the students themselves. Lack of self-motivation to follow the learning process.